Law enforcement and syringe services program implementation in rural counties in Kentucky: a qualitative exploration - Sean T. Allen; Sarah Danforth; Suzanne M. Grieb; Jennifer L. Glick; Samantha J. Harris; Catherine Tomko; Susan G. Sherman (BMC, 2022)
Abstract Background Existing research in urban areas has documented a multitude of ways in which law enforcement may affect risks for bloodborne infectious disease acquisition among people who inject drugs (PWID), such as via syringe confiscation and engaging in practices that deter persons from accessing syringe services programs (SSPs). However, limited work has been conducted to explore how law enforcement may impact SSP implementation and operations in rural counties in the United States. This creates a significant gap in the HIV prevention literature given the volume of non-urban counties in the United States that are vulnerable to injection drug use-associated morbidity and mortality. Objective This study explores the influence of law enforcement during processes to acquire approvals for SSP implementation and subsequent program operations in rural Kentucky counties. Methods From August 2020 to October 2020, we conducted eighteen in-depth qualitative interviews among persons involved with SSP implementation in rural counties in Kentucky (USA). Interviews explored the factors that served as barriers and facilitators to SSP implementation and operations, including the role of law enforcement. Results Participants described scenarios in which rural law enforcement advocated for SSP implementation; however, they also reported police opposing rural SSP implementation and engaging in adverse behaviors (e.g., targeting SSP clients) that may jeopardize the public health of PWID. Participants reported that efforts to educate rural law enforcement about SSPs were particularly impactful when they discussed how SSP implementation may prevent needlestick injuries. Conclusions The results of this study suggest that there are multiple ways in which rural SSP implementation and subsequent operations in rural Kentucky counties are affected by law enforcement. Future work is needed to explore how to expeditiously engage rural law enforcement, and communities more broadly, about SSPs, their benefits, and public health necessity.